ETOS KERJA PEDAGANG ETNIS TIONGHOA DAN KEBERHASILANNYA DALAM BERDAGANG DI KELURAHAN SAGO KECAMATAN SENAPELAN KOTA PEKANBARU - Suselfy Harsindi Putri; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The purpose of this research is to provide information and analyze the work ethic rate of Tionghoa Traders and the success rate of trading in Urban Village of Sago, Sub-district of Senapelan, Pekanbaru. This research is a quantitative research, analyzed and depicted in a decriptive way. The theory that is used is “The Orientation Theory of Social Values” by Kluckhohn. This research is conducted during November-December 2018. The sample for this research is 33 Tionghoa Traders in Urban Village of Sago, Sub-district of Senapelan, Pekanbaru. The sample is taken using census sampling technique and data is collected using questionnaire. The dependent variable of this research are success in trading, whereas the independent variable is traders work ethic. Data is analyzed using SPSS 16 and Microsoft Excel 2010. The result of this research shows that: (1) The work ethic of Tionghoa Traders consist of cultural value orientation; (2) The work ethic rate of Tionghoa Traders in Urban Village of Sago, Sub-district of Senapelan, Pekanbaru is high; (3) The success rate of trading in Urban Village of Sago, Sub-district of Senapelan, Pekanbaru is very high; (4) The data analysis indicated that there was a positive relation between work ethic and the success of trading with 0,087469543 correlation values and in a very low range of correlation.Keywords : Work Ethic, Success In Trading, Tionghoa Ethnic